Integrating CAD/CAE/CAM in Engineering Curricula: A Project-Based Learning Approach - Fábio A. O. Fernandes; Nilo Fuchter Júnior; Anderson Daleffe; Daniel Fritzen; Ricardo J. Alves de Sousa (Education Sciences, 2020)
Problem-based learning (PBL) approaches are well-accepted and disseminated and have been intensively employed in several engineering programs. This article aims to present a teaching experience in which PBL was applied in one course of a mechanical engineering graduation program. The PBL approach applied is described step-by-step as well as the goals and constraints related to Computer-Aided Design, Engineering and Manufacturing (CAD/CAE/CAM) technologies employed in this particular case. The evaluation process is described, as well as the quantitative results, and also the results obtained from questionnaires answered by the students at the end of the PBL experience. Additionally, the team’s technical success in solving the proposed CAD/CAE/CAM problems was also taken into account. This PBL approach provided the students with the required autonomy to develop their argumentative skills within the team, defending their ideas, and at the same time, promoting self-criticism and ethical and impartial judgment among the other team members.